Making the Most of Scarcity : Accountability for Better Water Management in the Middle East and North Africa - World Bank (World Bank, Washington, DC, 2012)
Most of the Middle East and North Africa (MENA) cannot meet current water demand. Many countries face full-blown crises, and the situation is likely to get even worse. Estimates show that per capita water availability will be cut in half by 2050, with serious consequences for aquifers and natural hydrological systems. Demand for water supplies and irrigation services will change as economies grow and populations increase, with an attendant need to address industrial and urban pollution. Some 60 percent of the region's water flows across international borders, further complicating the resource management challenge. Rainfall patterns are predicted to shift as a result of climate change. The social, economic, and budgetary consequences of these challenges are enormous. The supply of drinking water could become more erratic, necessitating greater reliance on expensive desalination technologies, and increasing drought would require emergency supplies brought by tanker or barge. Service outages would put stress on expensive network and distribution infrastructure. Unreliable sources of irrigation water would depress farmer incomes, economic and physical dislocation would increase with the depletion of aquifers and unreliability of supplies, and local conflicts could intensify. All of this would have short- and long-term effects on economic growth and poverty, exacerbate social tensions within and between communities, and put increasing pressure on public budgets.